Oral histiocytic sarcoma in a cat with mandibular invasion and regional lymph node metastasis - Stephani L Ruppert (SAGE Publishing, 2021)
Case summary An 11-year-old female spayed domestic medium-hair cat presented for dental prophylaxis, at which time no oral mass was appreciated. Fifteen days after a dental cleaning, a mass expanding the oral mucosa of the rostral mandible was identified. An incisional biopsy revealed that the oral mucosa was infiltrated by neoplastic round-to-spindloid mesenchymal cells arranged in streams and small, dense aggregates consistent with an undifferentiated sarcoma. The patient was managed medically for approximately 6 months following the diagnosis, but, owing to declining health, euthanasia was elected and a post-mortem examination was performed. On post-mortem examination, the previously described neoplastic cells were infiltrating the rostral mandible and had metastasized to the right submandibular lymph node. Immunohistochemistry performed during the postmortem examination found that neoplastic cells were positive for Iba-1, CD18 and CD204, and negative for MUM-1, S100, Melan-A and E-cadherin, favoring a diagnosis of oral histiocytic sarcoma. Although recently recognized in cats, feline oral histiocytic sarcoma is rare, the tumor’s immunohistochemical profile is unstandardized, and the tumor’s behavior and prognosis are unclear. The diagnosis is challenging if small incisional biopsies are submitted and the neoplasm is poorly differentiated. This case report discusses the clinical, macroscopic, microscopic and immunohistochemical features of oral histiocytic sarcoma in a cat with mandibular invasion and submandibular lymph node metastasis. Relevance and novel information Feline primary oral histiocytic sarcoma is rare and tumor behavior and prognosis are unclear. This report broadens the immunohistochemical features of the tumor and recognizes mandibular invasion and submandibular lymph node metastasis.